(untitled) (Nexo Revista Científica, 2024)
The photocatalytic activity of a suspension of commercial titanium dioxide (FN1), deposited on a porous ignimbrite stone, widely used as a construction material in Arequipa-Peru, was evaluated in order to generate surfaces with self-cleaning properties in urban buildings. The suspension was applied on one side of the ignimbrite substrate by two methods: spray-coating and brush-coating. To evaluate that its application does not alter the physical aspect of the ignimbrite substrate surface, the color coordinates were determined by the CieL*a*b* method, after the application of FN1 giving a maximum total variation of 2.49, showing a good visual compatibility of the coating with the ignimbrite surface. The photocatalytic activity was evaluated by using photobleaching tests with the dyes 2,6-dichloroindophenol (DCIP) and methylene blue (AM), under simulated sunlight irradiation. The highest photocatalytic efficiency was obtained with the ignimbrite substrate coated with 3 layers by spraying FN1, which showed a photodegradation of AM and DCIP of 75.07% and 100% at 120 min and 5 min of irradiation, respectively.